Analysis and Interpretation of Customer Lifetime Value Insmall and Medium Enterprise Business Sustainability Strategies - Yuanisa Risqi Cahyani; Febrian Kwarto (Return : Study of Management, Economic and Bussines, 2026)
This study aims to analyze the Customer Lifetime Value (CLV) and its significance as the foundation for formulating business sustainability strategies in traditional herbal (jamu) micro and small enterprises (MSMEs). A mixed-method approach with a sequential explanatory design was employed: the quantitative phase calculated CLV using the RFM method from 30 active customers, followed by a qualitative phase involving in-depth interviews with 6 informants (business owner, sales representative, and customers). The results show that several product categories have the highest CLV and contribute the most to revenue. The interviews reveal that customer loyalty is influenced by trust in the benefits of herbal products, product quality, and the close relationship between the owner and customers. The findings lead to sustainability strategies that focus on high-value customer segments through customer retention efforts, simple transaction recording, and gradual digitalization of marketing activities. This study demonstrates that CLV can serve as a strategic tool to support business sustainability in traditional jamu MSMEs.